“PENUH ROH KUDUS” KUASA RESISTENSI: TAFSIR KPR 4: 1-22 DALAM PERSPEKTIF POSKOLONIAL SUBALTERN GAYATRI CAKRAVOTI SPIVAK - Aliyanto, Deky Nofa (Sekolah Tinggi Teologi Berea, Salatiga, 2024)
AbstractThe horizon of interpretation of Kpr 4: 1-22 is predominantly based on a theological perspective (Christological, soteriological and missiological) with a critical historical approach to analyzing the text of the holy book. In a society at any time and anywhere, socio-political aspects are an integral and significant part that shapes the dynamics and social structure of society. So that within the framework of religion and society, the religious mystical experience of being